Forming Youth Policy: The Experience of Kazakhstan - Kenzhegaliyevna Kenzhebayeva, Dana; Nuralievna Ospanova, Aigerim; Gazizovna Urmurzina, Bayan; Batyrzhanovich Abdullin, Ruslan (Opción, 2019)
Both the present and the future of any country depend on the socialization of its youth. As a result, state and society as a whole determine the appropriate directions of life activity aimed at promoting the social formation of the youth. At a certain stage of development, new structures form, which perform a specific function, i.e. implement a set of tasks that are united under the name "youth policy". The article analyzes different approaches to defining the concept and content of such categories as "state youth policy" and "youth policy". We have proved that the state is the main subject implementing youth policy and analyzed the Chinese experience in this sphere. The article presents the results of the sociological research entitled "Attitudes towards youth policy and the study of the needs and interests of young people in Almaty", which is the basis of the corresponding conclusions. We have also concluded that the formation of youth policy in modern conditions requires the active involvement of young people who are full-fledged members of society and should take an active part in its life.